The right thing - Waddle, Scott; Abraham, Ken. (Nashville, TN : Integrity Publishers, 2002)
"The untold story of the deadly collision of the nuclear submarine USS Greenville with a Japanese fishing vessel, and one man's courageous decision to do the right thing."
Keywords: Waddle, Scott; United States. -- Navy -- Officers -- Biography; Submarine captains -- United States -- Biography; Greeneville (Submarine); Ehime Maru (Training ship); Collisions at sea -- Hawaii; Submarine disasters -- Hawaii